2018
DOI: 10.1093/ons/opy277
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Clinical Microneurosurgical Experience With the 4K3-Dimensional Microvideoscope (ORBEYE) System for Microneurological Surgery: Observation Study

Abstract: BACKGROUND The exoscope has been reported as a novel neurosurgical instrumentation in clinical practice. OBJECTIVE To investigate the possibility that ORBEYE (OE), a novel instrument that excludes eyepiece lenses and allows for microsurgery by observation of the 4K3D monitor, could replace microscopes. METHODS We report 22 clinical cases by 5 experienced neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 17 publications
3
94
0
Order By: Relevance
“…Recently, the exoscope has been proposed as an alternative to the microscope in the field of neurosurgery. [1][2][3][4][5][26][27][28][29][30][31][32] One of the merits of exoscopes, including ORBEYE, is that they are superior to microscopes in terms of ergonomic features. The advantage of our method mainly depends on the excellence of the ergonomic operability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the exoscope has been proposed as an alternative to the microscope in the field of neurosurgery. [1][2][3][4][5][26][27][28][29][30][31][32] One of the merits of exoscopes, including ORBEYE, is that they are superior to microscopes in terms of ergonomic features. The advantage of our method mainly depends on the excellence of the ergonomic operability.…”
Section: Discussionmentioning
confidence: 99%
“…The usefulness of exoscopes, including ORBEYE (Olympus, Tokyo, Japan), which was recently introduced into neurosurgery, has been reported in several fields. [1][2][3][4] One of their merits is that they are superior to a conventional microscope in terms of ergonomic features. They do not limit the posture of the operator regardless of the angle of the operative visual axis, and we previously reported that ORBEYE facilitates ergonomic microsurgery with the angle of the operative visual axis approximately horizontal.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 2, there are increasing reports using digital microscope with 4K-3D camera since 2018 [2,10,11]. However, video microscopes with conventional 2K-3D cameras are still currently reported [12,13,14,15,16,17,18,19]. Notably, our report was the first utilizing a video microscope with 8K-UHD camera.…”
Section: Discussionmentioning
confidence: 79%
“…More recently, the high-definition exoscope has been reported as a novel instrumentation. 19) While few reports have described the use of such devices in CEA, their use seems likely to increase.…”
Section: Microsurgical Dissection Of the Carotid Artery Using Mini-homentioning
confidence: 99%